The Unbreakable Relations Between Indonesia-Vietnam Post “Sink the Vessels” Policy: A Complex Systems Approach - Rusadi Kantaprawira; Arry Bainus; Indra Kusumawardhana (JAS (Journal of ASEAN Studies), 2018)
The vibrant bilateral relations between Indonesia-Vietnam has been tested by the Sink the Vessels policy, a robust measure executed by Indonesia to tackle rampant illegal fishing that encroach Indonesian waters. The policy has caused in the demolition of, among else, Vietnamese fishing vessels; and has also led to near-clash and incidents at sea. Despite these, both countries bilateral relations were far from hostile condition, and uphold their neighbourly relations to manage the illegal fishing problem. How Could Indonesia’s foreign policy action did not further exacerbate Indonesia-Vietnam relations post “Sink the Vessels” policy? To tackle our question, this article probes to describe the complex systems that interwoven Indonesia and Vietnam during the rising tension. We argue that the complex systems encapsulated Indonesia – Vietnam relations post “Sink the Vessels” policy consist of symbol system, interest system, and role system that maintain their friendly bilateral relations, even in the turbulence ocean. This article exposes that Indonesia-Vietnam responds to tackle the problem stems primarily from the linkage between the three systems to escape the security dilemma.